2015
DOI: 10.1021/acs.langmuir.5b03702
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of the Liposome-Mediated Deintercalation of Anticancer Drug Doxorubicin from the Drug–DNA Complex: A Spectroscopic Approach

Abstract: Biocompatible liposomes were used for the first time to study the deintercalation process of a prominent anticancer drug, doxorubicin (DOX), from doxorubicin-intercalated DNA (DOX-DNA complex) under controlled experimental conditions. The study revealed that anionic liposomes (DMPG liposomes) appeared to be the most effective to bring in the highest percentage of drug release while cationic liposomes (DOTAP liposomes) scored the lowest percentage of release. The drug release was primarily attributed to the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
9
17
0
Order By: Relevance
“…We observed a biexponential lifetime decay of DOX in all of the liposomes. This observation is consistent with our recent report . The complex lifetime decay is primarily attributed to the heterogeneous distribution of the DOX molecules in the liposomes.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We observed a biexponential lifetime decay of DOX in all of the liposomes. This observation is consistent with our recent report . The complex lifetime decay is primarily attributed to the heterogeneous distribution of the DOX molecules in the liposomes.…”
Section: Resultssupporting
confidence: 94%
“…The intensity became almost saturated at around 0.8 and completely seized at 1 mM lipid concentration. The binding constants for DOX–liposome systems as estimated following our earlier publications (the detailed methodology is given in the Supporting Information) were 4.70 × 10 8 M –1 for DPPC liposomes, 2.70 × 10 8 M –1 for DMPC liposomes, and 2.90 × 10 8 M –1 for POPC liposomes (Figure e). We may explain the different binding constants of DOX with liposomes in terms of the structural difference of the hydrophobic chain length and hence their pretransition temperatures.…”
Section: Resultsmentioning
confidence: 95%
“…Time-resolved fluorescence anisotropy is also a very useful technique to determine the microenvironment and location of the probe in a multi-component environment. It gives an idea about structural and dynamical information of the fluorophore in an organized medium. , Fluorescence decay anisotropy is directly associated with the reorientation dynamics of the excited fluorophore, and thus it is a suitable tool for the investigation of molecular dynamics and rotational relaxation and thereby for the structural information of fluorophore . To obtain the information about the microenvironment around the NOS in different mediums (SDS micelle, ctDNA, and composite medium), the time-resolved fluorescence anisotropy decay of NOS was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Das et al also reported a similar type of results for PSF binding with ctDNA. 4 To confirm the exact binding mechanism of PIP to ctDNA, we performed the ethidium bromide (EB) fluorescence displacement experiment. EB is a well-known intercalating agent, and it binds between the base pairs of DNA, which cause enhancement of the fluorescence intensity.…”
Section: Resultsmentioning
confidence: 99%